Role of breeding and natal movements in lifetime dispersal of a forest‐dwelling rodent. Issue 7 (2nd March 2017) - Selonen, Vesa; Wistbacka, Ralf
Abstract: The lifetime movements of an individual determine the gene flow and invasion potential of the species. However, sex dependence of dispersal and selective pressures driving dispersal have gained much more attention than dispersal at different life and age stages. Natal dispersal is more common than dispersal between breeding attempts, but breeding dispersal may be promoted by resource availability and competition. Here, we utilize mark–recapture data on the nest‐box population of Siberian flying squirrels to analyze lifetime dispersal patterns. Natal dispersal means the distance between the natal nest and the nest used the following year, whereas breeding movements refer to the nest site changes between breeding attempts. The movement distances observed here were comparable to distances reported earlier from radio‐telemetry studies. Breeding movements did not contribute to lifetime dispersal distance and were not related to variation in food abundance or habitat patch size. Breeding movements of males were negatively, albeit not strongly, related to male population size. In females, breeding movement activity was low and was not related to previous breeding success or to competition between females for territories. Natal philopatry was linked to apparent death of a mother; that is, we did not find evidence for mothers bequeathing territories for offspring, like observed in some other rodent species. Our results give an example of a species in which breeding movements are not driven by environmental variability or nest site quality. Different evolutionary forces often operate in natal and breeding movements, and our study supports the view that juveniles are responsible for redistributing individuals within and between populations. This emphasizes the importance of knowledge on natal dispersal, if we want to understand consequences of movement ecology of the species at the population level. Abstract : Breeding movements are not driven by environmental variability or nest site quality in a forest rodent. Natal dispersers are responsible for redistributing individuals within and between populations.